2021
DOI: 10.1111/geb.13291
|View full text |Cite
|
Sign up to set email alerts
|

Multi‐decade tree mortality in temperate old‐growth forests of Europe and North America: Non‐equilibrial dynamics and species‐individualistic response to disturbance

Abstract: Aim Old‐growth, mesic temperate forests are often assumed to be structured by gap‐phase processes, resulting in quasi‐equilibrial long‐term dynamics. This assumption influences management focused on simulation of natural disturbance dynamics and is embedded in most models of forest successional dynamics. We use multi‐decade monitoring of permanent plots in old‐growth forests to assess demographic assumptions directly with respect to tree mortality rates. Location Sixteen sites in mesic, temperate old‐growth fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(21 citation statements)
references
References 107 publications
(240 reference statements)
2
19
0
Order By: Relevance
“…Given the scarcity of old-growth and direct long-term monitoring of tree populations from permanent plot data in the temperate region of Europe, there are few studies that allow direct comparison with our results. Consistent with our findings, a recent assessment of multi-decade mortality rates in mesic, temperate old-growth forests in eastern North America and Europe found that mortality rates were variable over time, with long-term averages higher than previous published estimates (i.e., generally c. 1%/year), results which were partly attributed to the occurrence of rare disturbance events (Woods et al, 2021). In a long-term study of mortality rates from permanent plots in mixed forests across Switzerland, Etzold et al…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Given the scarcity of old-growth and direct long-term monitoring of tree populations from permanent plot data in the temperate region of Europe, there are few studies that allow direct comparison with our results. Consistent with our findings, a recent assessment of multi-decade mortality rates in mesic, temperate old-growth forests in eastern North America and Europe found that mortality rates were variable over time, with long-term averages higher than previous published estimates (i.e., generally c. 1%/year), results which were partly attributed to the occurrence of rare disturbance events (Woods et al, 2021). In a long-term study of mortality rates from permanent plots in mixed forests across Switzerland, Etzold et al…”
Section: Discussionsupporting
confidence: 92%
“…We build on the study of Woods et al (2021) using a network of small old-growth remnants located across temperate mountain forests of Slovenia, where long-term observations of tree populations have been carried out in permanent plots since the 1980s. We quantify multi-decade rates and drivers of tree demography, using data on mode of mortality and disturbance observations to disentangle background and disturbance related mortality.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The development of an automated learning algorithm is underway. The size of canopy gaps is important factor and indicator in forest ecosystems [72]. Propagation vectors of invasive plant species are also traceable in the sample areas using aerial remote sensing [11].…”
Section: Complex Evaluation Optionsmentioning
confidence: 99%
“…However, for the top of the trees or canopy structure, the flight altitude can cause considerable perspective distortions. Due to the strong perspective distortion of the The size of canopy gaps is an important factor and indicator in forest ecosystems [72]. Propagation vectors of invasive plant species are also traceable in the sample areas using aerial remote sensing [11].…”
Section: Geometric Accuracy Of Hramnmentioning
confidence: 99%